Configurations for Achieving Organizational Ambidexterity with Digitization - Park, YoungKi; Pavlou, Paul A.; Saraf, Nilesh (Information Systems Research, 2020)
Organizational ambidexterity refers to the capability of businesses to balance the pursuit of radical innovation simultaneously with incremental innovation. It echoes the popular notion that to thrive well in a competitive economy, businesses need to balance their exploration of new markets and products with exploitation or balance operational efficiency with flexibility. Digital technologies have become central to enabling organizational ambidexterity. The analysis reveals how the three dimensions of digitization efforts—IT implementation spending, IT training, and actual IT usage—should be combined with specific internal and external factors to develop greater ambidexterity. Two of these complementary factors are either a centralized organizational structure or a strong supplier and partner network—the first a likely channel for cross-organizational knowledge transfer and the second for interfirm knowledge transfers. However, determining which combinations are useful also depends on the size of the business and competitiveness of markets. Large businesses, or those in more competitive sectors, derive a slightly greater advantage from digitization than small firms or those in less competitive sectors. These findings are useful for policy makers tasked with subsidy allocation to industry sectors and managers when allocating investment spending for digitization.